Real-world effectiveness and persistence of secukinumab in the treatment of patients with psoriatic arthritis - Alegre-Sancho, Juan José; Núñez-Monje, Victoria; Campos-Fernández, Cristina; Balaguer-Trull, Isabel; Robustillo-Villarino, Montserrat; Aguilar-Zamora, Marta; Garijo-Bufort, Marta; Pedraz-Penalva, Teresa; Peña-González, Carolina; de la Morena, Isabel; Bedoya-Sanchís, Diego; Yankova-Komsalova, Liliya; et al. (Frontiers in Medicine, 2023)
Introduction Psoriatic arthritis (PsA) is a complex and heterogeneous inflammatory disease. Secukinumab, a biologic disease-modifying antirheumatic drug (bDMARD), has extensive clinical evidence of efficacy and safety in the treatment of PsA but data in clinical practice are still limited. This study aims to provide real-world evidence on secukinumab use, effectiveness, and persistence in PsA. Methods A retrospective, multicenter study was conducted on patients diagnosed with PsA and treated with secukinumab up to June 2021 at 12 centers in the Valencian Community (Spain). Data on DAS28-CRP, DAPSA, Tender and Swollen Joint Counts (TJC, SJC), enthesitis, dactylitis, skin and nail involvement, pain, patient and physician global assessment (ptGA, phGA) using 100-mm visual analog scale (VAS), and persistence for up to 24 months were collected. Results A total of 178 patients were included (49% men; mean [standard deviation, SD] age: 51.4 [10.5] years; 39% obese). Secukinumab was used as a first-, second-, or ≥ third-line bDMARD in 37, 21, and 42% of patients, respectively. The percentage of patients achieving at least low disease activity (DAS28-CRP ≤ 3.2) increased from 25% at baseline to 66% at month 6 (M6) and was maintained (75%) up to M24. Mean (SD) DAS28-CRP baseline values (3.9 [1.2]) decreased to 2.9 (1.1) (p < 0.001) at M6 and remained low through M24 (2.6 [1.1]) (p < 0.001). Secukinumab also improved peripheral arthritis increasing the percentage of patients with TJC = 0 (20% baseline; 57% M24) and SJC = 0 (37% baseline; 80% M24). Treatment reduced the percentage of patients with enthesitis (25% baseline; 6% M24), dactylitis (20% baseline; 4% M24), and skin (70% baseline; 17% M24), and nail (32% baseline; 2% M24) involvement. Additionally, we observed improvements in the mean pain VAS (−26.4 mm M24), ptGA (−26.2 mm M24), and phGA (−24.8 mm M24). Secukinumab showed an overall 24-month persistence rate of 67% (95% confidence interval [CI]: 60–74%). Patients receiving first-line secukinumab showed the highest 24-month persistence rate (83, 95% CI: 73–92; p = 0.024). Conclusion Secukinumab showed long-term effectiveness across the six key PsA domains thus reducing disease activity and pain, which are major treatment goals. This was accompanied by high persistence rates, especially in bDMARD naive patients.